2019
DOI: 10.1002/mnfr.201900492
|View full text |Cite
|
Sign up to set email alerts
|

ω‐3 PUFAs Alleviate High‐Fat Diet–Induced Circadian Intestinal Microbes Dysbiosis

Abstract: Scope Published data support that fish oil and algae oil rich in ω‐3 polyunsaturated fatty acids (PUFAs) protect against hyperlipidemia in mice. This study is aimed to explore the effects of fish oil and algae oil on high‐fat diet (HFD) induced circadian intestinal microbes dysregulation. Methods and Results Male C57BL/6 mice are randomly divided into four groups, which are fed a normal chow diet (CON), a HFD, a HFD supplemented with fish oil (FO), and a HFD supplemented with algae oil (AO), respectively, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Gut microbiota analysis also reveals changes in DIO mice, characterized by a reduction in the Bacteroidetes phylum and an increase in the Firmicutes phylum (34). A few previous studies also tested the circadian rhythmicity of gut microbiota, and suggested distinct differences between normal mice and DIO mice (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 93%
“…Gut microbiota analysis also reveals changes in DIO mice, characterized by a reduction in the Bacteroidetes phylum and an increase in the Firmicutes phylum (34). A few previous studies also tested the circadian rhythmicity of gut microbiota, and suggested distinct differences between normal mice and DIO mice (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 93%
“…In view of the relationship between microbiota and health and disease, gut microbiota has been used as a subjective measurement for disease and its treatment ( 15 , 16 ). The few human and animal studies showed that omega-3 PUFA supplementation has an impact on the composition of the gut microbiota ( 17 , 18 ). Moreover, the beneficial role of omega-3 PUFA supplementation in behavioral disorders may be through regulation of the composition of intestinal microbiota ( 19 ), although the research on this topic is still in its initial stages.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…Finally, a large body of literature shows that the protective effects exerted by Omega-3 PUFAs in various diseases may be in part related to their capacity to affect gut microbiota composition and dysbiosis [171]. These fatty acids are reported to influence environmental factors (such as antibiotic, drug, or overnutrition stress) that are able to upset the balance of gut microbiota, causing dysbiosis [8,[171][172][173][174][175][176] and, in turn, induce the development of a series of pathologies. As we noted (Section 3.1), several studies have demonstrated decreased diversity and dysbiosis of the microbiota present at the level of the injured skin.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%